2021
DOI: 10.3389/fnbot.2021.728327
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Acute Vs. Chronic Patients With Spinal Cord Injury With a Neurologically Controlled Hybrid Assistive Limb Exoskeleton: Is There a Difference in Outcome?

Abstract: This study aimed to assess the outcome of acute and chronic participants with spinal cord injury (SCI) after 12 weeks of bodyweight supported treadmill training (BWSTT) with a hybrid assistive limb exoskeleton (HAL). Acute participants were defined as ≤12 months between SCI and training, chronic participants >12 months between SCI and training. We assessed whether HAL-assisted BWSTT is advantageous for acute and chronic participants and if length of time post injury impacts the outcome of HAL-assisted B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…A comparative analysis of the investigated group and control group showed a significantly greater effect of RAGT on MS and WISCI-II parameters compared to S0. This study confirmed the improvement in these parameters previously reported in the literature, both in patients using exoskeletons alone and in patients using Lokomat alone [12,[33][34][35]. Alshram et al, in a meta-analysis concerning the impact of RAGT devices such as Lokomat, found that this therapy did not always improve MS scores [16].…”
Section: Discussionsupporting
confidence: 89%
“…A comparative analysis of the investigated group and control group showed a significantly greater effect of RAGT on MS and WISCI-II parameters compared to S0. This study confirmed the improvement in these parameters previously reported in the literature, both in patients using exoskeletons alone and in patients using Lokomat alone [12,[33][34][35]. Alshram et al, in a meta-analysis concerning the impact of RAGT devices such as Lokomat, found that this therapy did not always improve MS scores [16].…”
Section: Discussionsupporting
confidence: 89%
“…The authors of [ 45 ] assessed the outcome of acute and chronic participants with spinal cord injury after 12 weeks of bodyweight-supported treadmill training with a hybrid assistive limb exoskeleton. The study included 110 participants (89 males and 21 females), with an average age of 44.3 years, ranging from 16 to 74 years.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the study’s design does not allow for an acceptable inferential analysis, necessitating follow-up clinical studies to evaluate the posed theory. Zieriacks et al [ 45 ] The Ten Meter Walk Test result, which measures ambulation speed, is more clinically applicable. In the Ten Meter Walk Test, acute and chronic subjects dramatically increased their test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zieriacks et al. [18] compared outcomes of HAL walking rehabilitation between patients with acute and chronic spinal cord injury. Patients with acute and chronic spinal cord injury both showed significant recovery of walking parameters, including results for 10 m and 6 min walking tests, and improvement in WISCI-II score.…”
Section: Introductionmentioning
confidence: 99%